Peritoneal mesothelioma and malignant lymphoma in mice caused by fibrous zeolite. Issue 11 (November 1985) - Ozesmi, M; Patiroglu, T E; Hillerdal, G; Ozesmi, C
Abstract : Dust from the village of Karain containing the fibrous zeolite erionite, talc, and physiological saline were tested by intraperitoneal injection in 486 Swiss albino mice. Malignant tumours were found in 84 (41 mesotheliomas, 31 lymphomas, 1 peripheral epidermoid carcinoma, and 11 lymphomas and mesotheliomas together) of the 321 animals which died spontaneously within nine to 32 months after injection of Karain dust (26.1%). Three mesotheliomas and no lymphomas were found among 24 animals injected in the same way with talc during the same time (12.5%). In 46 control animals injected with physiological saline three mesotheliomas and one lymphoma were seen (8.7%). Thus Karain dust appears to be a potent carcinogen, causing both mesotheliomas and malignant lymphomas.